2000
DOI: 10.1038/sj.bjp.0703265
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral cannabinoid modulation of gastrointestinal transit in physiological states or during the diarrhoea induced by croton oil

Abstract: , i.p.) but not by SR144528 (52 nmol mouse 71 , i.p.) both in control and croton-oil treated mice. 5 Ganglionic blockade with hexamethonium (69 nmol mouse 71 , i.p.) did not modify the inhibitory eect of i.p.-injected cannabinoid agonists either in control or in croton-oil treated mice. 6 The lower ED 50 values of cannabinoid drugs after i.c.v. administration suggest a central (CB 1 ) site of action. However, a peripheral site of action is suggested by the lack of eect of hexamethonium. In addition, croton oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 31 publications
(57 reference statements)
10
83
2
1
Order By: Relevance
“…For example they inhibit GI transit and motility in rats (Landi et al, 2002), decrease the intragastric pressure and the pyloric contractility by activating CB 1 receptors (Krowicki et al, 1999), tonically inhibit colonic propulsion (Pinto et al, 2002) and decrease GI transit in mice (Izzo et al, 2000). CB 1 receptor agonists decreased the gastric acid secretion induced by pentagastrin given intravenously (Adami et al, 2002), but i.c.v.…”
Section: Discussionmentioning
confidence: 99%
“…For example they inhibit GI transit and motility in rats (Landi et al, 2002), decrease the intragastric pressure and the pyloric contractility by activating CB 1 receptors (Krowicki et al, 1999), tonically inhibit colonic propulsion (Pinto et al, 2002) and decrease GI transit in mice (Izzo et al, 2000). CB 1 receptor agonists decreased the gastric acid secretion induced by pentagastrin given intravenously (Adami et al, 2002), but i.c.v.…”
Section: Discussionmentioning
confidence: 99%
“…In another study of LPS-induced inflammation, the FAAH inhibitor AM3506 normalized hypermotility in a CB 1 -and CB 2 -dependent manner, whereas colonic propulsion was CB 1 -dependent [21]. Interestingly, the effect of cannabinoids in cases of inflammatory hypermotility occurred at lower doses than in control states [8,22]. This could be due to the increased receptor expression during inflammation, to increased coupling of the receptor to effectors proteins, or both.…”
Section: Role Of the Ecs In Gut Homeostasismentioning
confidence: 98%
“…It is well established that cannabinoids exert a braking effect on physiological GI transit, inhibiting gastric emptying and motility (Shook and Burks, 1989;Izzo et al, 1999b;Krowicki et al, 1999), upper GI transit (Shook and Burks, 1989;Colombo et al, 1998;Izzo et al, 1999aIzzo et al, , 2000Izzo et al, , 2001Landi et al, 2002;Mathison et al, 2004), and colonic propulsion , through the activation of CB 1 receptors. In the current study, through the use of specific CB 1 and CB 2 receptor antagonists, we confirmed the CB 1 -mediated inhibitory action of WIN55212-2 on GI tract motility and colonic propulsion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have attempted to elucidate, through the use of varying routes of drug administration and/or vagotomy or ganglionic blockade, the role that central versus peripheral CB receptor activation plays in the modulation of GI motility. Their findings revealed evidence that suggests there may be regional differences such that CB 1 receptors located in the vago-vagal circuitry mediate the actions in slowing gastric motility (Krowicki et al, 1999), whereas mainly peripheral CB 1 receptors mediate the inhibitory actions on GI transit (Landi et al, 2002), and either central or peripheral CB 1 receptors can mediate the slowing of upper GI transit and colonic propulsion (Izzo et al, 2000;Pinto et al, 2002).…”
Section: Introductionmentioning
confidence: 99%